2019
DOI: 10.3389/fimmu.2019.02004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Glycolylneuraminic Acid (Neu5Gc) and Its Glycosides

Abstract: Sialic acids constitute a family of negatively charged structurally diverse monosaccharides that are commonly presented on the termini of glycans in higher animals and some microorganisms. In addition to N -acetylneuraminic acid (Neu5Ac), N -glycolyl neuraminic acid (Neu5Gc) is among the most common sialic acid forms in nature. Nevertheless, unlike most animals, human cells loss the ability to synthesize Neu5Gc although Neu5Gc-containing glycoconjugates have been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 169 publications
1
44
0
1
Order By: Relevance
“…N-acetylneuraminic acid (Neu5Ac) is one of the commonly distributed natural carbohydrates, and it is also a basic component of many glycoproteins, including glycopeptides and glycolipids, with a wide range of biological functions [12]. Moreover, the biochemical derivatives of Neu5Ac are also commonly used in the synthesis of medications [12]. Recent studies showed that Neu5Ac may participate in the pathogenesis of atherosclerosis by promoting immune inflammatory response [13,14], regulating lipoprotein metabolism [15], enhancing insulin resistance [16], accelerating thrombosis formation [17], and stimulating vascular smooth muscle cell proliferation and apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-acetylneuraminic acid (Neu5Ac) is one of the commonly distributed natural carbohydrates, and it is also a basic component of many glycoproteins, including glycopeptides and glycolipids, with a wide range of biological functions [12]. Moreover, the biochemical derivatives of Neu5Ac are also commonly used in the synthesis of medications [12]. Recent studies showed that Neu5Ac may participate in the pathogenesis of atherosclerosis by promoting immune inflammatory response [13,14], regulating lipoprotein metabolism [15], enhancing insulin resistance [16], accelerating thrombosis formation [17], and stimulating vascular smooth muscle cell proliferation and apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detection of some metabolites may be helpful for clarifying the pathophysiological mechanism of the disease [ 11 ]. N-acetylneuraminic acid (Neu5Ac) is one of the commonly distributed natural carbohydrates, and it is also a basic component of many glycoproteins, including glycopeptides and glycolipids, with a wide range of biological functions [ 12 ]. Moreover, the biochemical derivatives of Neu5Ac are also commonly used in the synthesis of medications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated Neu5Gc loading among human cells (8,9); however, further studies are warranted to establish whether indeed a substantial fraction of humans actually lack the fundamental component of the theoretical basis of the xenosialitis model. Although Neu5Gc exists at trace levels on ECs of positive individuals, we must also consider the myriad of surface glycoproteins or lipoproteins that display Neu5Gc and the high diversity of Neu5Gc terminal residues, which result in a huge dispersion of cell-surface epitopes that are potentially recognized by A-GcAbs (15). It is thus possible that, following interactions with A-GcAbs, the coexistence of trace levels of antigens and the high epitope dispersion results in physiological cellular signaling that is below the activation threshold.…”
Section: Levels Of Neu5gc-loading Among Human Cells With Diet-derivedmentioning
confidence: 99%
“…The most extensive variety of sialosides, containing Ac and Gc forms as well as other modifications, for use on microarrays and in other applications has been derived by the laboratory of Xi Chen (Yu et al, 2005, 2006a,b, 2011; Chokhawala et al, 2008; Linman et al, 2012; Khedri et al, 2014; Li et al, 2017). This work uses novel one-pot synthesis and combinatorial methods, and is the subject of another review in this issue (Chen et al, 2019). The diversity and biological applications of large libraries of natural and non-natural sialosides and their chemical approaches were well described in previous reviews (Deng et al, 2013; Liang et al, 2015).…”
Section: Diversity Of Glycan Microarray Platformsmentioning
confidence: 99%